Comparison of Different Surgical Methods for Necrotizing Pancreatitis: A Meta-Analysis - Xiao, Jianguo; Quan, Xiaojiao; Liu, Fang; Li, Wen (Frontiers in Surgery, 2021)
Purpose To compare the effectiveness and safety of three methods of open necrosectomy, minimally invasive surgery and endoscopic step-up approach for necrotizing pancreatitis. Methods We searched Pubmed, embase, ScienceDirect and CNKI full text database (CNKI) (to December 25, 2019). RCT, prospective cohort study (PCS) and retrospective cohort study (RCS) comparing the effectiveness and safety of any two of above-mentioned three methods were included. Results There was no significant difference in major complications or death, and mortality between the minimally invasive surgery treatment group and the endoscopic step-up approach treatment group (RR=1.66, 95%CI:0.83-3.33, P=0.15; RR=1.05, 95%CI:0.59-1.86, P=0.87); the incidence rate of new-onset multiple organ failure, enterocutaneous fistula, pancreatic-cutaneous fistula, intra-abdominal bleeding and endocrine pancreatic insufficiency in the endoscopic step-up approach treatment group was significantly lower than minimally invasive surgery group (RR=2.65, 95%CI:1.10-6.36, P=0.03; RR=6.63, 95%CI:1.59-27.60, P=0.009; RR=7.73, 95%CI:3.00-19.89, P<0.0001; RR=1.91, 95%CI:1.13-3.24, P=0.02; RR=1.83, 95%CI:1.9-3.16, P=0.02); hospital stay in the endoscopic step-up approach group was significantly shorter than minimally invasive surgical treatment group (MD=11.26, 95%CI:5.46-17.05, P=0.0001). The incidence of pancreatic-cutaneous fistula in the endoscopic escalation step therapy group was significantly lower than that in the open necrosectomy group (RR=0.11, 95%CI:0.02-0.58, P=0.009). Conclusion Compared with minimally invasive surgery and open necrosectomy, although endoscopic step-up approach cannot reduce the main complications or death and mortality of patients, it can significantly reduce the incidence of some serious complications, such as pancreatic-cutaneous fistula, enterocutaneous fistula, intra-abdominal bleeding, endocrine pancreatic insufficiency, and can significantly shorten the patient's hospital stay.